2009
DOI: 10.1002/cbic.200900142
|View full text |Cite
|
Sign up to set email alerts
|

6‐Amino‐6‐deoxy‐5,6‐di‐N‐(N′‐octyliminomethylidene)nojirimycin: Synthesis, Biological Evaluation, and Crystal Structure in Complex with Acid β‐Glucosidase

Abstract: Abstract6‐Amino‐6‐deoxy‐5,6‐di‐N‐(N′‐octyliminomethylidene)nojirimycin, a reducing analogue of N‐nonyl‐1‐deoxynojirimycin, proved to be a potent and very selective inhibitor of β‐glucosidases, including human acid β‐glucosidase. Structural studies of the enzyme–inhibitor complex showed a binding mode in which the anomeric hydroxy group is accommodated in the “wrong” α configuration.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Formation of the enzyme-inhibitor complex was, however, entropically driven, a thermodynamic signature that is unique for this family of sugar mimics. Further X-ray structural studies on the interaction of the 6-amino-6-deoxy-5,6-di-N-(N'-octyliminomethylidene)nojirimycin analogue (6N-NOI-NJ, 3; Scheme 1) with recombinant human b-glucocerebrosidase confirmed a binding mode analogous to that previously encountered for NN-DNJ, [39] with additional interactions involving the pseudoanomeric hydroxyl group. The rigid bicyclic framework imposes a restricted orientation of the hydrophobic substituent that is probably responsible for the unprecedented anomeric selectivity.…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…Formation of the enzyme-inhibitor complex was, however, entropically driven, a thermodynamic signature that is unique for this family of sugar mimics. Further X-ray structural studies on the interaction of the 6-amino-6-deoxy-5,6-di-N-(N'-octyliminomethylidene)nojirimycin analogue (6N-NOI-NJ, 3; Scheme 1) with recombinant human b-glucocerebrosidase confirmed a binding mode analogous to that previously encountered for NN-DNJ, [39] with additional interactions involving the pseudoanomeric hydroxyl group. The rigid bicyclic framework imposes a restricted orientation of the hydrophobic substituent that is probably responsible for the unprecedented anomeric selectivity.…”
Section: Introductionsupporting
confidence: 50%
“…[49] The remarkable selectivity for b-Glu was ascribed to the rigidity of the bicyclic skeleton. [39] Since the synthesis of sp 2 iminosugars is readily amenable to molecular diversity-oriented strategies and biological activity optimization, evaluation of their potential as chemical chaperones for the treatment of Gaucher disease was very appealing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, unusual structures such as bicyclic nojirimycin derivatives 7 and a lipophilic derivative of isofagomine 8 have also been found to exert excellent activities in this context. Other laboratories such as Wong's 9 as well as Aerts and Overkleeft and their co-workers 10 have observed that large, lipophilic N-alkyl substituents, in particular adamantyl-substituted spacer arms, provide excellent interaction between the inhibitor and the lysosomal β-glucosidase.…”
Section: Introductionmentioning
confidence: 99%